Evaluating comparative performance of Indian engineering educational institutes based on TQM criteria for internal benchmarking. Issue 1 (10th January 2019) - Mehta, Namish; Diwakar, Nilesh; Arya, Rajeev
Abstract : Purpose: The purpose of this paper is to provide a framework for designing a multiple performance measurement tool for evaluating, comparing and benchmarking the working of engineering educational institutes in a group based on total quality management (TQM) criteria and performance measurement criterion, respectively. Design/methodology/approach: Proposed framework is based on fuzzy analytic hierarchy process (FAHP) which takes in to account the fuzziness of human opinion for realistic outcome and generalization of the results. Based on the proposed framework a case study was conducted on engineering institutes of central India for collecting data and analyzing the current practices followed in these institutes. A relationship among TQM implementation criterion was developed, their respective weights derived and then institutes were ranked. Findings: It was found that the rank of institutions based on both the criterion is same, which indicates that the institutes having better TQM implementation have better performance. Research limitations/implications: The research in this paper is limited to Indian scenario; studies in other countries and sectors may be conducted to compare the results obtained. Practical implications: The results will help policy makers in identifying institutions having poor performance in the region. Originality/value: The paper is navel in its attempt to provide a model based on TQM criteria for evaluating the working of engineering educational institutes in a group in terms of their relative weightage and benchmark.